Permeable concrete brick with reserved groove and manufacturing method and analysis method thereof
By designing semicircular grooves in permeable concrete bricks and optimizing material ratios, the problem of weakening of the mechanical properties of existing permeable bricks is solved, better permeability and mechanical properties are achieved, and the service life of the bricks is extended.
Patent Information
- Application Number
- CN202411847753.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-25
AI Technical Summary
The groove structure of existing permeable bricks significantly weakens the mechanical properties of the bricks, resulting in a reduced water permeability and a shortened service life.
A permeable concrete brick with semicircular grooves is designed, with the composition including 5% sand rate, 10% silica fume dosage, and 4% alkali exciter dosage. By optimizing the material ratio and groove shape, the permeability and mechanical properties of the brick body are improved.
The bricks are well permeable and have high mechanical properties, extending service life and reducing the risk of blockage.
Smart Images

Figure CN119683912A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of building materials, and in particular relates to a permeable concrete brick with a reserved groove and a manufacturing method and an analysis method thereof. Background Art
[0002] Permeable Concrete Paving Brick (PCPB), as a new type of sustainable pavement material, has been widely used in various occasions of urbanization construction due to its excellent environmental and economic benefits. Common permeable bricks on the market include ceramic permeable bricks, sand-based permeable bricks, and cement permeable bricks. They have a certain ability to absorb and permeate water, but their permeability is limited. When the precipitation is too large, they cannot quickly drain rainwater into the ground. In addition, as the service time increases, impurities mixed in the rainwater gradually block the permeable holes, and the permeability continues to decrease, no longer meeting the permeability requirements.
[0003] In recent years, domestic and foreign scholars have developed various new permeable paving bricks that can meet the permeability requirements and discharge rainwater into the ground in time. The reduction in permeability after long-term service can also meet the requirements. However, most of them have complex preparation processes, great construction difficulties, poor economic effects, and are difficult to apply to physical projects.
[0004] Therefore, it is necessary to provide a new type of permeable concrete brick to solve the above technical problems. Summary of the invention
[0005] The technical problem to be solved by the present invention is that the groove structure of the permeable brick in the prior art significantly weakens the mechanical properties of the brick body.
[0006] The present invention solves the above-mentioned problem by adopting the following technical solution:
[0007] A permeable concrete brick with a reserved groove, comprising 5% sand, 10% silica fume, and 4% alkali activator. The brick body is provided with a groove, which is a through groove with a semicircular cross-section. The pavement brick has a compressive strength of 35.3 MPa, a splitting tensile strength of 4.5 MPa, and a water permeability coefficient of 0.301 cm / s.
[0008] Compared with the prior art, the present invention adopting the above structure has the following beneficial effects:
[0009] First of all, the brick body is made of permeable concrete, which uses coarse aggregate and medium sand as the main raw materials, cement and silica fume as adhesives, and appropriate amounts of water reducers and alkali activators as admixtures. After molding, gaps are formed between the aggregates, and rainwater can flow into the ground along the gaps, which has the characteristics of good permeability.
[0010] Secondly, the brick body design adopts a bottom groove form. The semicircular groove shortens the seepage path and increases the water permeability of the brick body. At the same time, it solves the risk of pore blockage during the long-term service of the brick body and extends its service life.
[0011] Preferably, the grooves are all located above the center of the lower surface of the brick body and are symmetrical about the center of the lower surface of the brick body, the groove width is one third of the width of the brick body, and the groove height is less than one half of the height of the brick body.
[0012] The present invention solves the above problem and also provides a method for making the above-mentioned pavement bricks. The specific technical solution is as follows:
[0013] A method for manufacturing a permeable concrete brick with a reserved groove is carried out according to the following steps:
[0014] 1) Weigh the corresponding mass of coarse aggregate and medium sand in turn, and pour them into the mixer and stir for 30 seconds;
[0015] 2) Pour half of the total mass of water into the blender and stir thoroughly for 30 seconds;
[0016] 3) Weigh the corresponding mass of cement and add it into the mixer and stir for 30 seconds;
[0017] 4) Weigh the corresponding amount of silica fume and add it into a blender and stir for 30 seconds;
[0018] 5) Weigh the corresponding mass of high-efficiency water reducer and alkali activator, mix them thoroughly with the remaining water, slowly pour them into the blender and stir for 90 seconds;
[0019] 6) Pour into a customized mold, manually vibrate and shape, and demould after standing at room temperature for 24 hours;
[0020] 7) Demould and cure in an environment of 20±2℃ and 95% humidity.
[0021] The present invention also provides a comprehensive performance analysis method for permeable concrete bricks with reserved grooves:
[0022] A. Analysis through finite element compression simulation:
[0023] The first step is sample selection: the size of the sample permeable bricks is 200mm×100mm×60mm, and grooves of different shapes are set on the bottom of the permeable bricks. The shapes of the grooves are rectangular, semicircular, three-center arch, circular arch and trapezoidal;
[0024] The second step is meshing: select solid65 unit to establish the finite element model, and select the unit size as 10mm; adopt sweeping meshing, use mesh200 unit to mesh the source surface and the target surface, and perform mesh encryption near the groove;
[0025] Step 3: Constitutive relation and failure criterion: Use the WW failure criterion of concrete in the ANSYS system and input relevant parameters. Turn off the concrete crushing option, that is, set the compressive strength value to -1. When writing the APDL command stream, enter the command in the command stream window:
[0026] tb,concr,1,1,
[0027] tbdata,,0.5,0.95,ft,-1,
[0028] Thus, the relevant parameters of the failure criterion of concrete are determined; input stress-strain data to define the constitutive relationship of PCPB as MISO model, select the default linear elastic model, continue to input stress-strain data to define the constitutive relationship of PCPB as MISO model; replace the descending section in the stress-strain curve with a flat line with a slope of zero;
[0029] Step 4: Loading and solving: Apply uniform surface load perpendicular to the upper surface of the PCPB model to simulate pressure; apply z-direction constraint on the lower surface of the brick to simulate ground constraint; apply x, y, and z-direction constraints at the edge of the lower surface of the brick, select static analysis as the solution type, perform piecewise linearization in each loading increment, select the convergence criterion of force as the convergence criterion, and use the system default value of 0.5% for the convergence tolerance;
[0030] The fifth step is to obtain the finite element calculation results: through trial calculation, the load step is set to 1, the load sub-step is set to 500 steps, and the PCPB compression simulation with different groove shapes is carried out. A surface load of 10MPa is applied to different PCPB models. After the calculation is completed, the Von Mises stress cloud map and the displacement cloud map in the Y direction are exported in the post-processor module;
[0031] Step 6: Take the test piece and put it into the electro-hydraulic servo universal testing machine for compression test. The loading rate is 0.5 MPa per second. The structural strength of the new PCPB is calculated by the following formula; the average value of each group of 5 bricks is taken as the structural strength value of the group.
[0032]
[0033] in:
[0034] Rcs——structural strength value of new PCPB (MPa);
[0035] P——destruction load of new PCPB (N);
[0036] A——upper bearing area of new PCPB (mm 2 ),
[0037] The groove shape with better pressure performance is obtained;
[0038] Step 7: Take out the test pieces after the test damage, and analyze the bearing capacity of the brick body of each reserved groove according to the damage of each test piece;
[0039] C. Analysis of the influence of groove shape on water permeability loss rate:
[0040] Step 8: Before the test, seal the corners of the brick with a small amount of lightweight clay, and then wrap the sides of the brick with multiple layers of plastic film;
[0041] The ninth step is to place the specimen into the water permeability coefficient measuring device, turn on the tap, and measure the original water permeability coefficient of the specimen using the fixed water test method. After the measurement is completed, take out the specimen;
[0042] Step 9: Wait for the water inside the brick to completely drain out, wipe off the water on its surface, put the specimen back into the water permeability coefficient measuring device, evenly spread 20g of fine sand on the upper surface of the brick, slowly drip water into the instrument, during which the water hits the surface of the brick in a dripping state, continue dripping water for 2 minutes, then turn on the faucet to allow the water to evenly flush the entire brick;
[0043] Step 10, repeat the above process five times, and measure the water permeability coefficient of PCPB after five simulated blockages according to the constant water head test method;
[0044] D. Effect of groove shape on antifreeze performance:
[0045] Step 11, based on the calculated results of the compressive strength loss rate of PCPB with different groove shapes, the groove shape was plotted for 50 freeze-thaw cycles;
[0046] The twelfth step is to compare the permeable concrete bricks with grooves and the permeable concrete bricks without grooves, and calculate the compressive strength loss rate of the permeable concrete bricks after reserving the grooves. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 The PCPB seepage path comparison before and after grooving of the present invention;
[0048] Figure 2 It is the cross section of permeable concrete brick
[0049] Figure 3 Embodiments of various groove shapes;
[0050] Figure 4 It is a cross-sectional view of the groove shape of each embodiment;
[0051] Figure 5 Grid division diagram for source and target surfaces;
[0052] Figure 6 Grid division diagram for the new PCPB;
[0053] Figure 7 Schematic diagram of load placement and constraints;
[0054] Figure 8 Von Mises stress cloud diagrams of different groove opening shapes: (a) rectangular, (b) semicircular, (c) three-center arch, (d) circular arch, and (e) trapezoid;
[0055] Fig. 9 The displacement diagrams of different groove shapes under compression in the Y direction are: (a) rectangular, (b) semicircular, (c) three-center arch, (d) circular arch, and (e) trapezoid;
[0056] Fig.10 The effect of groove shape on the strength of PCPB structure;
[0057] Fig.11 Comparison of the failure of specimens with different grooves under compression test, (a) semicircular groove, (b) rectangular groove;
[0058] Fig.12 The influence of groove shape on the water permeability loss rate;
[0059] Fig.13 The influence of groove shape on the water permeability loss rate (a) no groove; (b) rectangle; (c) semicircle; (d) three-center arch; (e) circular arch; (f) trapezoid;
[0060] Fig.14 Effect of groove shape on compressive strength loss rate. DETAILED DESCRIPTION
[0061] The present invention will be further described below in conjunction with embodiments, the purpose of which is only to provide a better understanding of the content of the present invention. Therefore, the examples given do not limit the protection scope of the present invention.
[0062] The water permeability and mechanical properties of permeable concrete bricks (PCPB) are two mutually restrictive performance indicators, that is, the improvement of water permeability will inevitably lead to a decrease in brick strength. According to Darcy's permeability law:
[0063]
[0064] Where Q is the brick seepage rate per unit time, k is the brick permeability coefficient, A is the brick cross-sectional area perpendicular to the water flow direction, h2-h1 is the head difference, and L is the seepage path length.
[0065] See also Figure 1By reserving a groove at the bottom of the PCPB, the partial seepage path L of water in the brick body is shortened, the seepage volume per unit time is increased, and the water permeability performance will be improved. However, the structural bearing capacity of the permeable brick will decrease due to the changes in shape and structure. Therefore, it is necessary to conduct a comprehensive study on the mechanical parameters and water permeability of the new PCPB with reserved grooves, so as to determine the optimal material ratio and groove shape combination scheme.
[0066] Material mix design:
[0067] PCPB needs to have good water permeability and air permeability, and the porosity is directly related to the water permeability of PCPB. Therefore, in the process of mix design, the porosity should be guaranteed to a certain extent. The present invention refers to the "Technical Specification for Permeable Cement Concrete Pavement" (CJJ / T135-2009) and adopts a three-factor three-level orthogonal test method to carry out the mix design of PCPB, and uses the volume method to calculate the specific amount of each material:
[0068]
[0069] Where:
[0070] Mca, Ms, Mc, Msf, Mw, Msp, Maa——the amount of coarse aggregate, medium sand, cement, silica fume, water, water reducer and alkali activator required to prepare 1m3 PCPB (kg);
[0071] ρca, ρs, ρc, ρsf, ρw, ρsp, ρaa——density of coarse aggregate, medium sand, cement, silica fume, water, water reducer, alkali activator (kg / m 3 );
[0072] P——target porosity (%);
[0073] Rs——sand ratio (%);
[0074] Rw / c——water-cement ratio.
[0075] The water-cement ratio of the PCPB of the present invention is 0.30, medium sand is added in a manner of replacing part of the coarse aggregate by equal volume of 0%, 5%, and 10%, silica fume is added in a manner of replacing part of the cement by equal volume of 0%, 5%, and 10%, and alkali activator is added in a manner of replacing part of the cementitious material by equal mass of 0%, 2%, and 4%. Specific mix ratio parameters are listed in Table 1, and the porosity of the obtained brick body is 15%.
[0076] Table 1 PCPB detailed mix parameters
[0077]
[0078] In order to test the mechanical properties, the experimental samples were prepared. According to the above mix ratio and specific parameters, the PCPB with a specification of 200mm×100mm×60mm was prepared by cement-wrapped stone method. The specific process is as follows:
[0079] 1) Weigh the corresponding mass of coarse aggregate and medium sand in turn, and pour them into the mixer and stir for 30 seconds;
[0080] 2) Pour half of the total mass of water into the blender and stir thoroughly for 30 seconds;
[0081] 3) Weigh the corresponding mass of cement and add it into the mixer and stir for 30 seconds;
[0082] 4) Weigh the corresponding amount of silica fume and add it into a blender and stir for 30 seconds;
[0083] 5) Weigh the corresponding mass of high-efficiency water reducer and alkali activator, mix them thoroughly with the remaining water, slowly pour them into the blender and stir for 90 seconds;
[0084] 6) Pour into a customized mold, manually vibrate and shape, and demould after standing at room temperature for 24 hours;
[0085] 7) Demould and cure in an environment of 20±2℃ and 95% humidity.
[0086] The following is a mechanical properties analysis of multiple experimental samples with different components to find the optimal dosage ratio:
[0087] 1. According to the provisions of the Chinese national standard "Permeable Brick" (JC / T 945-2005), the test samples were placed in an electro-hydraulic servo universal testing machine, and the test samples were evenly loaded at a loading rate of 0.05MPa / s to conduct a compressive strength test.
[0088] 2. According to the provisions of China's national standard "Permeable Pavement Bricks and Permeable Road Slabs" (GB / T 25993-2010), the tensile strength test was carried out by uniformly loading the test sample at a loading rate of 0.05MPa / s until the test sample was damaged.
[0089] 3. With reference to the Chinese national standard "Permeable Pavement Bricks and Permeable Road Slabs" (GB / T 25993-2010), the experimental samples are placed in a constant water head permeability test device that meets the test standards to conduct permeability coefficient testing. Before the test, the edges of the experimental samples must be sealed with plastic film and lightweight clay so that water can only penetrate through the upper and lower surfaces of the experimental samples.
[0090] The specific test results of each index are listed in Table 2.
[0091] Table 2 PCPB test results
[0092]
[0093]
[0094] About compressive strength: The compressive strength of PCPB increases with the increase of silica fume content. On the one hand, the particle size of silica fume is smaller than that of cement, the specific surface area is larger, and the micro-aggregate effect is significant. Therefore, the addition of silica fume can fill the harmful gaps between cement pastes, make the pore distribution inside the brick more uniform, and improve the pore structure of hardened cement paste; on the other hand, the addition of silica fume promotes the secondary hydration reaction (volcanic ash reaction) of cement, forms more dense CSH gel, and improves the compressive strength of PCPB. With the increase of the amount of alkali activator, the compressive strength of PCPB increases slightly. This is because under the stimulation of the alkali activator, the volcanic ash reaction process is accelerated, producing more fine zeolite-like products and more CSH gel, thereby enhancing the compressive strength of the permeable brick. The best level of each factor for the compressive strength of PCPB is: sand ratio 5%, silica fume content 10%, and alkali activator dosage 4%.
[0095] Regarding tensile strength: the influence of three factors at different levels on tensile strength, with the increase of sand ratio, the tensile strength first increases and then decreases; the tensile strength increases with the increase of silica fume content; with the continuous increase of alkali activator dosage, the tensile strength shows a slowly rising trend. For tensile strength, the optimal factor level is 5% sand ratio, 10% silica fume content, and 4% alkali activator dosage, which is almost consistent with the conclusion drawn from compressive strength.
[0096] Regarding the water permeability coefficient: it decreases with the increase of sand ratio. This is because the addition of fine aggregates such as medium sand will fill some of the pores inside the brick body, making the brick structure denser, and the water permeability of the brick body mainly depends on the number of pores, so the addition of medium sand reduces the water permeability coefficient of PCPB. After the addition of silica fume, the water permeability coefficient of the permeable brick did not change significantly. This is because silica fume is added in the form of equal volume to replace cement, which has almost no effect on the pores in the brick body, so the amount of silica fume added has almost no effect on the water permeability coefficient. With the increase of the amount of alkali activator, the water permeability coefficient of the permeable brick has a tendency to rise slowly. This is because the alkali activator solution has high hydrophilicity, which enhances the ability of PCPB to attract water molecules, resulting in an increase in the water permeability coefficient. For the water permeability coefficient, the optimal factor levels are 0% sand ratio, 10% silica fume content, and 4% alkali activator dosage.
[0097] Analysis results:
[0098] Based on the above range and variance analysis of the test results, the compressive strength, splitting tensile strength and water permeability coefficient of PCPB were comprehensively considered, and the strength of PCPB was guaranteed as much as possible while meeting the requirements of the specification. Therefore, the optimal dosage was selected as follows: sand ratio 5%, silica fume dosage 10%, and alkali activator dosage 4%. PCPB was prepared according to the optimal dosage of each material, and the obtained PCPB had a compressive strength of 35.3MPa, a splitting tensile strength of 4.5MPa, and a water permeability of 0.301cm / s, all of which met the requirements of the specification.
[0099] The preferred groove shape design of permeable bricks:
[0100] First, prepare the experimental sample with reserved groove (hereinafter referred to as the test piece):
[0101] 1. Paste a small test block on the bottom of the mold. The shape of the small test block is made according to the design to reserve grooves to make permeable concrete brick experimental samples with different groove shapes;
[0102] 2. The size of a single PCPB is 200mm×100mm×60mm. The required material amounts are shown in Table 3. Weigh the corresponding mass of the stirred mixture according to the mix ratio in the table, slowly pour it into a homemade mold, and form it.
[0103] Table 3 Material consumption of a single piece of new PCPB
[0104]
[0105] 3. After demoulding, transfer to a curing room with PCPB standard curing conditions (relative humidity 95%, temperature 20±2°C) and cure for 28 days to obtain a new PCPB specimen.
[0106] The present invention studies different preset groove shapes to determine the best permeable brick type with groove shape, and implements sample production according to the preferred dosage ratio described in the above analysis. The size of the sample permeable brick is 200mm×100mm×60mm, and grooves of different shapes are set on the bottom of the permeable brick, such as Figure 2 , Figure 3 As shown, the first embodiment is rectangular, the second embodiment is semicircular, the third embodiment is a three-center arch, the fourth embodiment is a circular arch, and the fifth embodiment is a trapezoid. The grooves of each embodiment have the same volume, are all located above the center of the lower surface of the brick body, and are all symmetrical about the center of the lower surface of the brick body.
[0107] Comprehensive performance analysis method of permeable concrete bricks with reserved grooves:
[0108] A. Analysis of the new PCPB by finite element compression simulation:
[0109] The first step is sample selection: select the above-mentioned examples 1 to 5 as analysis samples.
[0110] The second step is meshing: select solid65 units to establish a finite element model and define relevant material properties. Since the accuracy of the finite element simulation can be guaranteed when the mesh size is 10mm, the unit size is selected as 10mm. After selecting the mesh size, it is necessary to specify the way to divide the mesh. ANSYS software provides three meshing methods: adaptive division, mapping division, and sweep division. The present invention adopts sweeping division and uses mesh200 units to perform mesh division of the source surface and the target surface. The characteristic of mesh200 units is that they only participate in the meshing work but do not have the degrees of freedom, material properties, and real constants of ordinary units. Once the unit is not needed, it can be deleted or left in the model without participating in the calculation, and will not affect the calculation results. Taking into account that the surrounding brick body after the reserved groove is relatively weak, the mesh near the groove is encrypted. Taking the embodiment of the semicircular groove as an example, the mesh division of the source surface and the target surface is as follows Figure 4 As shown in Figure 2, the PCPB model after partitioning is as follows: Figure 5 shown.
[0111] The third step is constitutive relations and failure criteria. Use the WW failure criteria of concrete in the ANSYS system and input relevant parameters. Turn off the concrete crushing option, that is, set the compressive strength value to -1. When writing the APDL command stream, enter the command in the command stream window:
[0112] tb,concr,1,1,
[0113] tbdata,,0.5,0.95,ft,-1.
[0114] In this way, the relevant parameters of the failure criterion of concrete are determined. The default linear elastic model is still used for its constitutive relationship. Therefore, it is necessary to continue to input stress-strain data to define the constitutive relationship of PCPB as the MISO model to achieve a better fitting effect. It should be noted that the MISO model requires that the tangent slope of the first stress-strain point of the constitutive relationship curve input by the user must correspond to the elastic modulus value of the material, and in versions after ANSYS13.0, the MISO model curve is not allowed to have a tangent slope greater than the elastic modulus or less than zero (in fact, the constitutive relationship of concrete has a descending section), otherwise the program will report an error and the calculation cannot be performed. Considering the difficulty of obtaining the descending section of the PCPB constitutive relationship curve by the test instrument itself and the small influence of the descending section in the ANSYS analysis, the descending section in the stress-strain curve is replaced by a flat line with a slope of zero to ensure the correct calculation of the program.
[0115] Step 4: Loading and solving: According to the actual compression situation, the present invention applies a uniform surface load perpendicular to the upper surface downward on the upper surface of the PCPB model to simulate pressure; applies a z-direction constraint on the lower surface of the brick body to simulate ground constraints; in order to avoid rigid body displacement, x, y, and z-direction constraints are applied to the edge of the lower surface of the brick body. The specific load distribution and constraint diagram is shown in the figure. Figure 6 As shown, the solution type is static analysis. Nonlinear static analysis essentially divides a complex loading process (actual working condition) into multiple loading increments (load steps), and performs piecewise linearization (load sub-steps) in each loading increment, that is:
[0116] Actual working condition = load step + load step + ...,
[0117] Load step = load sub-step + load sub-step + ….
[0118] The errors generated in the above calculation process are corrected by equilibrium iteration during solution. The default Newton-Raphson iteration method in the ANSYS program is used. This method can overcome the error accumulation in the direct iteration process and force equilibrium convergence at the end of each load increment. The convergence criterion is selected as the force convergence criterion, and the convergence tolerance uses the system default value of 0.5%.
[0119] Step 5: Get the finite element calculation results: To make the final calculation converge and the results accurate, the load step is set to 1 and the load sub-step is set to 500 through trial calculation, and the PCPB compression simulation with different groove shapes is carried out. A surface load of 10MPa is applied to different PCPB models. After the program calculation is completed, the Von Mises stress cloud map and the displacement cloud map in the Y direction are exported in the post-processor module. The results are shown in the figure. Figure 7 , Figure 8 As shown, it can be seen that the stress peak values and positions of PCPBs with different groove shapes are different, indicating that the groove shape is a factor affecting the compressive performance of the new PCPB, and the stress value near the groove is greater than the overall stress of the PCPB, indicating that the groove part (especially the top and bottom edges of the groove) is the weak part of the PCPB when it is under pressure and needs to be strengthened; the stress peak values of the rectangular, three-center arch, and circular arch groove PCPB appear at the top edge of the groove side wall, and the stress peak values of the semicircular and trapezoidal grooves appear at the bottom edge of the groove side wall; under the same load condition, the stress peak values of the semicircular and three-center arch grooves are smaller, indicating that the semicircular and three-center arch groove PCPBs have better compressive performance.
[0120] Through the above analysis, see Fig. 9It can be concluded that the overall Y-direction displacement value of the rectangular groove PCPB is large, the top of the groove is easily deformed under pressure, and the displacement cloud map of the groove part is not smooth. This is mainly due to the instability of the rectangular groove structure, which is more likely to deform during compression. The overall Y-direction displacement value of the semicircular groove PCPB is the smallest, and the displacement cloud map of the groove part transitions smoothly. This is because the semicircular groove structure is relatively stable and it is easier to maintain the original structural state when under pressure.
[0121] B. Bearing capacity test of PCPB structure with different groove shapes:
[0122] The sixth step is to take the test piece of the permeable concrete brick and put it into the electro-hydraulic servo universal testing machine for compression test. The loading rate is 0.5 MPa per second. The structural strength of the new PCPB is calculated using the following formula, and the average value of each group of 5 bricks is taken as the structural strength value of the group.
[0123]
[0124] in:
[0125] Rcs——structural strength value of new PCPB (MPa);
[0126] P——destruction load of new PCPB (N);
[0127] A——upper bearing area of new PCPB (mm 2 ).
[0128] Results Fig.10 The structural strengths of the semicircular, three-center arch, and circular arc arch groove PCPBs are relatively large, which are 27.9MPa, 26.1MPa, and 25.8MPa, respectively. The structural strength of the semicircular groove PCPB is 11.2% higher than that of the rectangular groove PCPB. This is because the arc shape is not easy to produce stress concentration, which is more conducive to the stability of the brick structure. Under the same conditions, it can withstand higher loads and is more in line with the needs of engineering structures.
[0129] Step 7: Take out the test specimen after the test. Take the semicircular groove and rectangular groove PCPB as an example. Fig.11 It can be seen that the bottom edge of the circular groove of the PCPB is damaged first after being compressed, indicating that the stress at the bottom edge of the circular groove is greater than that at other parts. The cracks in the brick body are mainly concentrated in the groove, indicating that the stress at the groove of the new PCPB is relatively large when it is compressed. It is the weak part of the entire brick body and needs to be strengthened. This is consistent with the conclusion obtained from the stress cloud map during finite element simulation. It was found in the experiment that the groove width of the sample with better mechanical properties cannot exceed half of the width of the brick body. It is better when the groove width is one-third of the brick body, and the result when the groove height is less than half of the brick body height is better.
[0130] C. Analysis of the influence of groove shape on water permeability loss rate:
[0131] Step 8. Before the test, seal the corners of the brick with a small amount of lightweight clay, and then wrap the sides of the brick with multiple layers of plastic film.
[0132] The ninth step is to place the specimen into the water permeability measuring device, turn on the tap, and use the fixed water test method to measure the original water permeability of the specimen. After the measurement, take out the specimen.
[0133] The ninth step is to wait for the water inside the brick to completely drain out and wipe off the moisture on its surface. Put the specimen back into the water permeability coefficient measuring device, spread 20g of fine sand evenly on the upper surface of the brick, and slowly drip water into the instrument. During this period, the water will hit the surface of the brick in a dripping state. After the dripping continues for 2 minutes, turn on the faucet to allow the water to evenly flush the entire brick.
[0134] Step 10, repeat the above process 5 times, and measure the PCPB permeability coefficient after 5 simulated blockages according to the constant water head test method.
[0135] The calculation results of the water permeability loss rate of PCPB with different groove shapes are as follows: Fig.12 As shown in the figure, it can be seen that after 5 simulated blockage tests, the water permeability loss rate of the PCPB without grooves reached 88.68%, indicating that its internal pores were seriously blocked and the water permeability dropped sharply; the water permeability loss rates of the PCPB with semicircular, three-center arch, and arc arch grooves were relatively low, at 34.54%, 46.86%, and 44.21%, respectively, and they can still maintain a certain water permeability. This is because the arc shape has streamline properties. According to the Bernoulli principle, the flow rate of water flowing through the brick body increases, and the ability to flush the blockage is stronger. The water permeability loss of the PCPB with rectangular grooves is relatively large. This is because the rectangular cross-section structure is gentle and the ability to flush gravel is weak, but its water permeability is still better than that of the control group.
[0136] After the test, leave the brick to dry. Fig.13 It can be seen that the surface pores of the PCPB without grooves are almost completely filled with blockages, and it basically has no water permeability; while the outer side of the PCPB specimen with grooves is more seriously blocked, and there are fewer blockages in the center of the brick body. This is because the reserved groove is located at the center of the bottom of the brick body, and the blockages concentrated above the groove are quickly washed out of the brick body due to the accelerated water flow rate, so the blockage is relatively not serious. The blockage on the surface of the PCPB with semicircular grooves is relatively good, indicating that its long-term water permeability is better than other PCPBs.
[0137] D. Effect of groove shape on antifreeze performance:
[0138] According to the calculation results of the compressive strength loss rate of PCPB with different groove shapes, a graph showing the influence of groove shape on the compressive strength loss rate of PCPB after 50 freeze-thaw cycles is drawn, as shown in Fig.14 As shown in the figure, it can be seen that compared with the PCPB without grooves, the compressive strength loss rate of the new PCPB with grooves has increased to varying degrees, indicating that the antifreeze performance of the PCPB with grooves will be weakened to a certain extent. Among them, the compressive strength loss rate of the PCPB with semicircular grooves is relatively low, at 9.68%; the strength loss rate of the PCPB with rectangular grooves is the highest, reaching 13.94%, but still not exceeding 20%, meeting the requirements of the specification. This may be due to the increase in the surface area of the PCPB brick body after the grooves are excavated, the increase in the contact area between the brick body and water during the freezing and thawing process, and the increase in the frost heave force inside the brick body, making the structure more susceptible to damage; compared with the rectangular groove, the surface area of the semicircular groove is smaller, and the increase in the frost heave force caused by the increase in surface area is smaller, so the compressive strength loss rate is lower.
[0139] The calculation steps for comprehensive analysis of PCPB performance with different grooves using the entropy weight method are as follows:
[0140] (1) Constructing the original data matrix
[0141] This scheme selects six different groove shapes, including no groove, rectangle, semicircle, three-center arch, circular arch, and trapezoid, as the evaluation objects; since the wear resistance, sound absorption and noise reduction performance of PCPB will not change due to the change of groove shape, the compressive strength value, water permeability coefficient loss rate, and compressive strength loss rate after 50 freeze-thaw cycles are selected as indicators to characterize different aspects of PCPB performance. The original data matrix X = (x ij ) a×b , i=1,2,···,6,j=1,2,3, the sample index data in the constructed X matrix are shown in Table 4.
[0142] Table 4 Sample index values
[0143]
[0144]
[0145] (2) Positive processing of indicators
[0146] Since the indicators have different directions when representing the quality of the evaluated object, in practical applications, it is often expected that the values of certain indicators are as large as possible (positive indicators), as small as possible (reverse indicators), tend to a certain median value (median indicators) or maintain within a certain interval (interval indicators). If the indicators are not processed in the same direction, it will lead to deviations in the subsequent calculation of weights and dimensionless indicators. For this article, the permeability loss rate and compressive strength loss rate involved are both reverse indicators, and the inverse transformation is used to positively process the indicators:
[0147]
[0148] Where:
[0149] y ij ——Data value after forward processing;
[0150] x ij ——Original data value.
[0151] The data after positive processing are shown in Table 5.
[0152] Table 5 Index positive data
[0153]
[0154]
[0155] (3) Dimensionless processing of indicators
[0156] Due to the differences in dimensions and units between indicators, the contribution types of these indicators to the evaluated objects are inconsistent, so the indicators need to be dimensionless, mainly including extreme value method, standardization method, mean method and other methods, among which the most widely used is the standardization method. However, when using the extreme value method, the extreme value will have a greater impact on the weight; after standardization, the differences in the degree of variation of each indicator will be eliminated, so the two are not applicable in multi-indicator comprehensive decision analysis. This paper selects the mean method to process the indicators and eliminate the dimension effect through the data mean:
[0157]
[0158] Where:
[0159] z ij ——Data value after dimensionless processing;
[0160] ——The mean of each sample data of indicator j.
[0161] The data obtained after processing by the mean method are shown in Table 6.
[0162] Table 6 Data after dimensionless processing by the mean method
[0163]
[0164]
[0165] (1) Calculation of proportion: Calculate the contribution proportion of each indicator under different evaluation objects according to the following formula:
[0166]
[0167] Where:
[0168] u ij ——The proportion of the j-th indicator in the ith evaluated object.
[0169] (2) Calculation of entropy value, difference coefficient and weight: The entropy value, difference coefficient and weight of each indicator are calculated according to the following formula:
[0170]
[0171] in:
[0172] e j ——The entropy value of the jth indicator;
[0173] g j ——The coefficient of difference of the jth indicator;
[0174] w j ——The weight of the j-th indicator.
[0175] (3) Calculation of the comprehensive score of the evaluation object: Based on the weight value w of each indicator j and the dimensionless z ij Value, calculate the comprehensive score of each evaluation object:
[0176]
[0177] in:
[0178] s i ——The comprehensive score of the ith evaluation object.
[0179] PCPB different indicators of e j , g j 、w jThe calculation results are shown in Table 7. It can be seen from Table 7 that the weight value of the water permeability loss rate is the largest, which is 0.5566, followed by the compressive strength loss rate and compressive strength after 50 freeze-thaw cycles, indicating that the long-term water permeability of the new PCPB is more important than its strength and frost resistance. In the use of PCPB, attention should be paid to the reduction degree of its water permeability, regular maintenance should be done, blockages should be cleared, and the blockage degree of PCPB should be reduced as much as possible; at the same time, attention should be paid to the freeze-thaw damage of PCPB in severe cold areas, and modified materials should be used to improve the frost resistance of the brick body; for the compressive strength of PCPB, its strength should be improved as much as possible on the basis of meeting the requirements of the specifications to eliminate the possibility of brick body damage.
[0180] Table 7 e of each indicator j , g j 、w j value
[0181]
[0182] The comprehensive scores of PCPBs with different groove shapes are shown in Table 8. It can be concluded from Table 8 that the comprehensive scores of PCPBs with different groove shapes are different, indicating that the groove shape can affect the comprehensive performance of PCPB. Among them, the comprehensive score of PCPB with semicircular grooves is the highest, which is 1.2867, indicating that PCPB with semicircular grooves has the best comprehensive performance, with higher compressive strength, the lowest water permeability loss rate and lower compressive strength loss rate. The comprehensive scores of PCPB with semicircular, three-center arch and arc arch grooves are all higher than those of PCPB without grooves, indicating that the comprehensive performance of PCPB with these three groove shapes is improved compared with PCPB without grooves. The comprehensive score of PCPB with rectangular grooves is the lowest, which is only 0.7966, indicating that the rectangular groove shape weakens the performance of PCPB. The above results show that the semicircular groove is the optimal groove shape of the new PCPB, which can greatly improve the problem of reduced water permeability of PCPB at the cost of losing some strength.
[0183] Table 8 Comprehensive scores of PCPB with different groove shapes
[0184]
[0185]
[0186] Compared with traditional municipal paving bricks, this permeable concrete brick has the following advantages:
[0187] 1. The body of permeable concrete bricks is permeable, which can infiltrate rainwater into the ground faster during heavy rain, reducing the burden on the urban drainage system and improving the urban groundwater environment.
[0188] 2. The arched groove can shorten the seepage path while meeting the bearing capacity, increase the water permeability rate, reduce the risk of clogging, and ensure long-term water permeability.
[0189] 3. Compared with traditional pavement bricks, the lower belly groove design reduces the weight of the bricks and the labor intensity of workers, while also saving the amount of building materials and reducing the production cost. Compared with the new permeable bricks on the market in recent years, it can achieve the same permeable effect, but the production process is simple and easy to lay.
[0190] 4. The capillary pores and semi-open pores inside the brick can also absorb and store water, which can alleviate the urban heat island effect to a great extent.
[0191] The above description is only a preferred feasible embodiment of the present invention, and does not limit the scope of rights of the present invention. All equivalent changes made using the contents of the present specification and its drawings are included in the scope of rights of the present invention.
Claims
1. A permeable concrete brick with a reserved groove, characterized in that: Its components are 5% sand, 10% silica fume, and 4% alkali activator. The brick body is provided with a groove, which is a through groove with a semicircular cross-section. The pavement brick has a compressive strength of 35.3MPa, a splitting tensile strength of 4.5MPa, and a permeability coefficient of 0.301cm / s.
2. The permeable concrete brick with a reserved groove according to claim 1, characterized in that: The grooves are all located above the center of the lower surface of the brick body and are symmetrical about the center of the lower surface of the brick body. The width of the grooves is one third of the width of the brick body, and the height of the grooves is less than one half of the height of the brick body.
3. The method for manufacturing a permeable concrete brick with a reserved groove according to claim 1, characterized in that: 1) Weigh the corresponding mass of coarse aggregate and medium sand in turn, and pour them into the mixer and stir for 30 seconds; 2) Pour half of the total mass of water into the blender and stir thoroughly for 30 seconds; 3) Weigh the corresponding mass of cement and add it into the mixer and stir for 30 seconds; 4) Weigh the corresponding amount of silica fume and add it into a blender and stir for 30 seconds; 5) Weigh the corresponding mass of high-efficiency water reducer and alkali activator, mix them thoroughly with the remaining water, slowly pour them into the blender and stir for 90 seconds; 6) Pour into a customized mold, manually vibrate and shape, and demould after standing at room temperature for 24 hours; 7) Demould and cure in an environment of 20±2℃ and 95% humidity.
4. Comprehensive performance analysis method of the permeable concrete brick with reserved grooves according to claim 1: A. Analysis through finite element compression simulation: The first step is sample selection: the size of the sample permeable bricks is 200mm×100mm×60mm, and grooves of different shapes are set on the bottom of the permeable bricks. The shapes of the grooves are rectangular, semicircular, three-center arch, circular arch and trapezoidal; The second step is meshing: select solid65 unit to establish the finite element model, and select the unit size as 10mm; adopt sweeping meshing, use mesh200 unit to mesh the source surface and the target surface, and encrypt the mesh near the groove; Step 3: Constitutive relation and failure criterion: Use the WW failure criterion of concrete in the ANSYS system and input relevant parameters. Turn off the concrete crushing option, that is, set the compressive strength value to -1. When writing the APDL command stream, enter the command in the command stream window: tb,concr,1,1, tbdata,,0.5,0.95,ft,-1, Thus, the relevant parameters of the concrete failure criterion are determined; Input stress-strain data to define the constitutive relation of PCPB as MISO model. Select the default linear elastic model and continue to input stress-strain data to define the constitutive relation of PCPB as MISO model. Replace the descending segment in the stress-strain curve with a flat line with a slope of zero. Step 4: Loading and solving: Apply uniform surface load perpendicular to the upper surface of the PCPB model to simulate pressure; apply z-direction constraint on the lower surface of the brick to simulate ground constraint; apply x, y, and z-direction constraints at the edge of the lower surface of the brick, select static analysis as the solution type, perform piecewise linearization in each loading increment, select the convergence criterion of force as the convergence criterion, and use the system default value of 0.5% for the convergence tolerance; The fifth step is to obtain the finite element calculation results: through trial calculation, the load step is set to 1, the load sub-step is set to 500 steps, and the PCPB compression simulation with different groove shapes is carried out. A surface load of 10MPa is applied to different PCPB models. After the calculation is completed, the Von Mises stress cloud map and the displacement cloud map in the Y direction are exported in the post-processor module; Step 6: Take the test piece and put it into the electro-hydraulic servo universal testing machine for compression test. The loading rate is 0.5 MPa per second. The structural strength of the new PCPB is calculated by the following formula; the average value of each group of 5 bricks is taken as the structural strength value of the group. in: Rcs——structural strength value of new PCPB (MPa); P——destruction load of new PCPB (N); A——upper bearing area of new PCPB (mm 2 ), The groove shape with better pressure performance is obtained; Step 7: Take out the test pieces after the test damage, and analyze the bearing capacity of the brick body of each reserved groove according to the damage of each test piece; C. Analysis of the influence of groove shape on water permeability loss rate: Step 8: Before the test, seal the corners of the brick with a small amount of lightweight clay, and then wrap the sides of the brick with multiple layers of plastic film; The ninth step is to place the specimen into the water permeability coefficient measuring device, turn on the tap, and measure the original water permeability coefficient of the specimen using the fixed water test method. After the measurement is completed, take out the specimen; Step 9: Wait for the water inside the brick to completely drain out, wipe off the water on its surface, put the specimen back into the water permeability coefficient measuring device, evenly spread 20g of fine sand on the upper surface of the brick, slowly drip water into the instrument, during which the water hits the surface of the brick in a dripping state, continue dripping water for 2 minutes, then turn on the faucet to allow the water to evenly flush the entire brick; Step 10, repeat the above process five times, and measure the water permeability coefficient of PCPB after five simulated blockages according to the constant water head test method; D. Effect of groove shape on antifreeze performance: Step 11, based on the calculated results of the compressive strength loss rate of PCPB with different groove shapes, the groove shape was plotted for 50 freeze-thaw cycles; The twelfth step is to compare the permeable concrete bricks with grooves and the permeable concrete bricks without grooves, and calculate the compressive strength loss rate of the permeable concrete bricks after reserving the grooves.